-(6n-4)=-7(2n+3)+3n

Simple and best practice solution for -(6n-4)=-7(2n+3)+3n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(6n-4)=-7(2n+3)+3n equation:


-(6n-4)=-7(2n+3)+3n

We simplify the equation to the form, which is simple to understand
-(6n-4)=-7(2n+3)+3n

Remove unnecessary parentheses
-6n+4=-7*(2n+3)+3n

Reorder the terms in parentheses
-6n+4=+(-14n-21)+3n

Remove unnecessary parentheses
-6n+4=-14n-21+3n

We move all terms containing n to the left and all other terms to the right.
-6n+14n-3n=-21-4

We simplify left and right side of the equation.
+5n=-25

We divide both sides of the equation by 5 to get n.
n=-5

See similar equations:

| 13x+7x=106 | | 3(X*5)=120 | | 13x+7s=106 | | x^2+20=8 | | 2x+2=92 | | 12/x=2/50 | | -4+f=18 | | 3x-24+15=-18 | | 50+105x=14.75x | | 3x-24+15=18 | | 3.95+3b=33.80 | | -34=v+43-5v | | 2(2x+4)=-4(x-16) | | 57.2+a*x+b*yandx+y=1 | | 2.5x+20=3x-4 | | X-11=-6 | | -2x+18=3x+33 | | 45b=25 | | (7y-8)-(5+6y)=9 | | 7=35n | | 95+13x+5=3x+10 | | -5.2=3w-3.4w | | 300x^2-240x+32=0 | | 5-8.5x=6.7-7.5x | | 4m-15=33 | | 3z+3=4z-14 | | y=2x^2-5x-42 | | 2w(w+2w)=18 | | y=2x^2-5x-43 | | -5x(x+y)=20+3x | | 5-7=d | | 4(3x-2)+5x=6(2x+8)-12 |

Equations solver categories